Molecular Characterization and Expression Analysis of Two Acetylcholinesterase Genes From the Small White Butterfly Pieris rapae (Lepidoptera: Pieridae). Issue 5 (4th September 2018) - Jiang, Xing-Chuan; Jiang, Xiu-Yun; Liu, Su
Abstract: Acetylcholinesterases (AChEs) are essential for the hydrolysis of the neurotransmitter acetylcholine and play crucial roles in the termination of neurotransmission. AChEs are encoded by the ace genes. However, the ace genes from the small white butterfly, Pieris rapae (L.) (Lepidoptera: Pieridae), remained uncharacterized. In this study, two ace s ( Prace1 and Prace2 ) were identified from P. rapae . Prace1 encoded a PrAChE1 protein consisting of 694 amino acid residues, and Prace2 encoded the 638-amino-acid PrAChE2. The two identified PrAChEs both had features typical of AChEs, including the catalytic triad, choline-binding sites, an oxyanion hole, an acyl pocket, a peripheral anionic subsite, an FGESAG motif and 14 conserved aromatic amino acids. Phylogenetic analysis showed that Prace1 and Prace2 were clustered into two distinct groups: ace1 and ace2, respectively. The two Prace s were distributed on different genomic scaffolds: Prace1 on scaffold 156 and Prace2 on scaffold 430. Additionally, Prace1 consisted of three exons and two introns, whereas Prace2 consisted of six exons and five introns. One amino acid mutation (Gly324Ala) in PrAChE1 and two (Ser291Gly and Ser431Phe) in PrAChE2 were consistent with mutations in other insect AChEs that are associated with insecticide insensitivity. Both Prace1 and Prace2 were highly expressed at the fifth-instar larval stage and in the larval head, and the transcriptional levels of Prace1 were significantly higher than those of Prace2 in all of the tested life stages and tissues. This is the first report characterizing two ace genes in P. rapae . The results pave the way for functional study of these genes.